(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2025)
This biography of the author of The Wind in the Willows is a contribution to the field of existential psychobiography made famous by Sartre. The mood of The Wind in the Willows is blithe on the surface, but there are darker references to the many adversities in the life of its author, known to many people firstly as a man about town, and the secretary of the Bank of England. The book is an example of how creativity can detoxify the pain of loss, at least up to a limit: in Grahame’s case, the loss of a child by suicide.